The Elusive Search for Success: Defining and Measuring Implementation Outcomes in a Real-World Hospital Trial - Heather L. Shepherd; Heather L. Shepherd; Liesbeth Geerligs; Phyllis Butow; Phyllis Butow; Lindy Masya; Joanne Shaw; Melanie Price; Haryana M. Dhillon; Haryana M. Dhillon; Thomas F. Hack; Thomas F. Hack; et al. (Frontiers Media S.A., 2019)
Objective and Study Setting: Research efforts to identify factors that influence successful implementation are growing. This paper describes methods of defining and measuring outcomes of implementation success, using a cluster randomized controlled trial with 12 cancer services in Australia comparing the effectiveness of implementation strategies to support adherence to the Australian Clinical Pathway for the Screening, Assessment and Management of Anxiety and Depression in Adult Cancer Patients (ADAPT CP).Study Design and Methods: Using the StaRI guidelines, a process evaluation was planned to explore participant experience of the ADAPT CP, resources and implementation strategies according to the Implementation Outcomes Framework. This study focused on identifying measurable outcome criteria, prior to data collection for the trial, which is currently in progress.Principal Findings: We translated each implementation outcome into clearly defined and measurable criteria, noting whether each addressed the ADAPT CP, resources or implementation strategies, or a combination of the three. A consensus process defined measures for the primary outcome (adherence) and secondary (implementation) outcomes; this process included literature review, discussion and clear measurement parameters. Based on our experience, we present an approach that could be used as a guide for other researchers and clinicians seeking to define success in their work.Conclusions: Defining and operationalizing success in real-world implementation yields a range of methodological challenges and complexities that may be overcome by iterative review and engagement with end users. A clear understanding of how outcomes are defined and measured, based on a strong theoretical framework, is crucial to meaningful measurement and outcomes. The conceptual approach described in this article could be generalized for use in other studies.Trial Registration: The ADAPT Program to support the management of anxiety and depression in adult cancer patients: a cluster randomized trial to evaluate different implementation strategies of the Clinical Pathway for Screening, Assessment and Management of Anxiety and Depression in Adult Cancer Patients was prospectively registered with the Australian New Zealand Clinical Trials Registry Registration Number: ACTRN12617000411347.